'Good stories get lost in bureaucracy!' Cultural biases and information for co-production. Issue 2 (17th February 2023) - Baines, Sue; Bull, Mike; Antcliff, Val; Martin, Lynn
ABSTRACT: This paper is about evidencing the social value of co-produced public services. We use Mary Douglas's theory of cultural variation to frame conflicting assumptions about what kinds of information count as good and reliable. With its emphasis on active participation, equality and mutual decision-making, co-production fits what Douglas called an 'egalitarian' worldview. It aligns well with local, contextual, experiential forms of information such as storytelling. Yet in present-day public services, alternatives favour individual choice, hierarchical rules, or chance outcomes. It is comfortable but ineffective to share only information that meets the preferences of one worldview and fails to respond to others.